2021
DOI: 10.1200/jco.2021.39.15_suppl.e20024
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported efficacy and toxicity in CAR T-cell therapy for multiple myeloma via Internet-based platforms.

Abstract: e20024 Background: Chimeric antigen receptor (CAR) T-cell therapies are in clinical development for multiple myeloma (MM). Patient-reported outcomes (PRO) can provide valuable insights into how patients perceive the relative risks and benefits of these new therapies. This study aimed to evaluate CAR T-cell therapy in relapsed/refractory MM (RRMM) patients. Methods: We utilized HealthTree Cure Hub for Multiple Myeloma to analyze patient-reported data from 17 patients who participated in CAR T-cell clinical tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…22 Therefore, HealthTree Cure Hub practices a patient-input and medical consultant-verified approach to maximize the potential for population-based analyses and to draw reliable conclusions. As a result, we have published nine abstracts, seven to ASCO [23][24][25][26][27][28][29] and two to the American Association of Cancer Research, 30,31 and published one peer-reviewed manuscript in Dermatologic Therapy, 18 with others in preparation.…”
Section: Discussionmentioning
confidence: 99%
“…22 Therefore, HealthTree Cure Hub practices a patient-input and medical consultant-verified approach to maximize the potential for population-based analyses and to draw reliable conclusions. As a result, we have published nine abstracts, seven to ASCO [23][24][25][26][27][28][29] and two to the American Association of Cancer Research, 30,31 and published one peer-reviewed manuscript in Dermatologic Therapy, 18 with others in preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Although limited studies evaluating PROs for those undergoing CAR-T cell treatments have been reported, most of these studies detail CD19-directed CAR-T cell therapies and, to date, there have been no PRO studies for patients receiving CD30-directed CAR-T cell therapy. [11][12][13][14] To further characterize the impact of CD30-CAR-T treatments on the patient experience at our center, we collected PROs in subjects enrolled on this clinical trial and report on these results here.…”
Section: Introductionmentioning
confidence: 99%